PSYCHOLOGICAL CONDITION RESIDENTS OF COMMUNITY SOCIAL ENVIRONMENT KEPUTIH SURABAYA - Laily Dzihni Kharisma (Study Program Guidance and Counseling, Univesitas Pendidik, 2023)
Psychological is part of psychological science. Psychological health is very important in overall health. Psychology is a complex science. A psychological condition is a condition that can affect the daily life of an individual. This study aims to determine the psychological condition of the residents of the Pondok Sosial (Liponsos) Keputih Surabaya Environment. The method used in this study is a qualitative research method. The subjects or research samples amounted to 6 (six) people who were residents of the Pondok Sosial (Liponsos) Environment of Keputih Surabaya. From the observations and interviews that have been conducted, the residents feel that Liponsos is like a prison for them. Because they can't be free outside, they often feel bored and want to get out of Liponsos. Based on the results of data analysis, it can be concluded that the residents of Liponsos have various backgrounds of problems, with limited limitations because they are Cooperative ODGJ (Persons with Mental Disorders).